Kesadaran dan Lingkungan Kerja para Penjual Tanaman Hias, Satwa dan Komponen Lain-lain di Pasty, Kota Yogyakarta - Djaja Hendra (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
Easy to say but hard to implement. That's an expression that has roughly the same meaning as the awareness and environmental factors in the workplaces of the sellers of ornamental plants, animals and other components in 'Pasty' in the city of Yogyakarta. This research is to find out the extent to which awareness and environmental factors in the workplace are fully understood and understood by the salespeople. This study uses a Stratified Random Sampling technique for sellers who are stratified according to the type of merchandise they have. Of the various types of merchandise after the calculation, more than 85% of all registered sellers in 'Pasty' were present to sell, while the rest closed their stalls. From there, then the sellers of the various types of merchandise were taken data using a questionnaire at random while conducting observations and brief interviews if needed. The results of the research are as follows: first, if it is only the awareness factor of the sellers without being associated with other factors, the sellers of other components are the traders who are the most 'aware' of the importance of cleanliness in their work environment compared to sellers of other types of merchandise; Second, but if it is only environmental factors from the sellers without being associated with other factors, then ornamental plant sellers are the most 'aware' of the importance of cleanliness in their work environment compared to sellers of other types of merchandise; Third, if it is connected between awareness and environmental factors, sellers of ornamental plants, animals and other components are sellers of other components who are the most 'aware' of cleanliness in their work environment. Fourth, when combined for all types of merchandise, they are slightly more 'aware' of other component sellers than other traders. Additional note: It is well known that, for all types of trades take place below 50% regarding 'awareness' and 'environment' in their workplace. That means, all types of merchandise in 'Pasty' in the city of Yogyakarta need to get socialization about the need for awareness and the environment so that consumers are interested in buying and coming to 'Pasty' in the city of Yogyakarta. Keywords: awareness, environment, workplace, sellers